Rationale of using the dual chemokine receptor CCR2/CCR5 inhibitor cenicriviroc for the treatment of COVID-19. - Daniel Clark Files; Frank Tacke; Alexandra O'Sullivan; Patrick Dorr; William G Ferguson; William G Powderly (PLoS Pathogens, 2022)
Coronavirus Disease 2019 (COVID-19), caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), has created a global pandemic infecting over 230 million people and costing millions of lives. Therapies to attenuate severe disease are desperately needed. Cenicriviroc (CVC), a C-C chemokine receptor type 5 (CCR5) and C-C chemokine receptor type 2 (CCR2) antagonist, an agent previously studied in advanced clinical trials for patients with HIV or nonalcoholic steatohepatitis (NASH), may have the potential to reduce respiratory and cardiovascular organ failures related to COVID-19. Inhibiting the CCR2 and CCR5 pathways could attenuate or prevent inflammation or fibrosis in both early and late stages of the disease and improve outcomes of COVID-19. Clinical trials using CVC either in addition to standard of care (SoC; e.g., dexamethasone) or in combination with other investigational agents in patients with COVID-19 are currently ongoing. These trials intend to leverage the anti-inflammatory actions of CVC for ameliorating the clinical course of COVID-19 and prevent complications. This article reviews the literature surrounding the CCR2 and CCR5 pathways, their proposed role in COVID-19, and the potential role of CVC to improve outcomes.